Upgrading of the Abilities of Lecturers of State Management: Problems and Solutions - Kieu Oanh, Nguyen; Thuong, Do Huy; Ngoc, Tran Luu; Hua, Pham Van (VNU Journal of Science: Education Research; Vol 37 No 2, 2021)
Upgrading the abilities of lecturers of state management at the training institutions for cadres, civil servants and public employees is interested in and actively implemented by all authorities in the period of 2016 - 2020. Besides achievements, the upgrading of the abilities of lecturers of state management still has some shortcomings that need to be overcome in the next period. This article analyses the situation and then proposes some solutions so that the upgrading of the abilities of lecturers of state management will become more effective, contributing to the enhancing of the state management of the cadres, civil servants and public employees in our country today.